Stability analysis and stabilization control of a grid-forming VSC-HVDC system - Lu, Yi; Shi, Gang; Chen, Qian; Qiu, Peng; Zhou, Jianqiao; Yang, Renxin; Zhang, Jianwen (Frontiers in Energy Research, 2024)
As the penetration of the integrated intermittent and fluctuant new energy (e.g. wind and photovoltaic power) increases, the conventional grid-following voltage source converter (VSC)-based high voltage direct current (HVDC) transmission system faces the problem of interactive instability with the grid. To overcome these above issues, a novel grid-forming control strategy is proposed, which adopts the dynamic of DC capacitor to realize the function of self-synchronization with the grid. Moreover, the per-unit DC voltage can automatically track the grid frequency, acting as a phase locked loop. Next, the small-signal model of the grid-forming VSC-HVDC system is established, and the stability of the system is analyzed by the eigenvalue analysis method and the complex power coefficient method. In addition, the stabilization controller is proposed to the GFM control structure, which further enhances the grid-forming VSC-HVDC system's stability and helps to operate stably under both stiff and weak grid conditions. Research results show that the VSC-HVDC system under the proposed grid-forming control is able to work stably in both stiff and weak grids. The grid-forming VSC-HVDC system has strong robustness, and can remain stable operation with large range variation of the parameters in the current and voltage control loop. Simulations are carried out on the platform of the PSCAD/EMTDC to verify the proposed grid-forming control strategy.